Amor, família e poder: a complexidade das relações em Os bem-casados, de Godofredo Rangel - Bruna Rafaela Silva Tobias (2024)
The novel Os bem-casados by Godofredo Rangel offers a penetrating perspective on Brazilian society in the early 20th century, exploring the prevalence of a culture of appearances and its implications on social, familial, and romantic dynamics. This study aims to analyze how Rangel structures the narrative and some literary elements of this novel, with special attention to character development, in order to explore themes such as manipulation in power relations, the conflicting role of family relationships, and the different positions of women in a patriarchal society. The author's writing style, marked by meticulous description and attention to detail, amplifies the vividness of social representation. Therefore, this study aims to demonstrate that Os bem-casados is consolidated as a significant work that offers an important panorama of Brazilian society of the period, highlighting its relevance to Brazilian literary studies.